Oil-hydraulic power units - state of the art - Seabra, Eurico (2017)
Despite the evolution of electric drives and their undeniable advantages, hydraulic systems play an important role in today's technologies. Due to the ability to operate enormous power densities, industrial hydraulics are irreplaceable when large forces and binaries are required. Its importance can be characterized by the economy it represents and by the development potential associated with scientific interest. This paper summarizes the technologies used in the production of oil-hydraulic power, seeking to identify the trends of development and the research opportunities that come from the demands of the current developments.